Proceedings of the International Scientific and Practical Conference on Digital Economy (ISCDE 2019) 2019
DOI: 10.2991/iscde-19.2019.128
|View full text |Cite
|
Sign up to set email alerts
|

Economic deterministic ensemble classifiers with probabilistic output using for robust quantification: study of unbalanced educational datasets

Abstract: The overall goal of our work is to find economic and robust supervised machine learning methods which adequate to both individual and collective Student Performance Forecast (SPF). The individual SPF are subject of well-known classification methods but collective SPF is subject of quantification learning algorithms dealing with the novel task to predict the frequency of classes in tested sample e.g. a number of students with unsatisfactory grade. The need for revise of classification methods shows review of 86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Particularly, we have demonstrated that decentralized national education systems with school-based management do not automatically lead to a rise of education quality. We conclude that at the local and regional level MQE, a key part of system is the prediction of a new situation with the quality of learning, determined by the individual and collective achievements of students, which in turn are educational data mining problems resolving by the classification and quantification methods [6][7]. Obviously, the mass-line courses implement [8] and recent ubiquitous implementation of distance learning as consequence of COVID-19 pandemic, also requires the application of these methods.…”
Section: Fig 2 Diagram Of the Educational Quality Monitoring And Mamentioning
confidence: 99%
See 4 more Smart Citations
“…Particularly, we have demonstrated that decentralized national education systems with school-based management do not automatically lead to a rise of education quality. We conclude that at the local and regional level MQE, a key part of system is the prediction of a new situation with the quality of learning, determined by the individual and collective achievements of students, which in turn are educational data mining problems resolving by the classification and quantification methods [6][7]. Obviously, the mass-line courses implement [8] and recent ubiquitous implementation of distance learning as consequence of COVID-19 pandemic, also requires the application of these methods.…”
Section: Fig 2 Diagram Of the Educational Quality Monitoring And Mamentioning
confidence: 99%
“…It is usually said that these datasets are balanced. However, detailed study of the student performance forecasts [7] showed that reviewed above high values of A were most often caused by imbalance of educational data samples. Indeed, our entire education systems are set up in such a way that the number of students N+ is much higher than N-Then, if the binary classifier mistakenly categorizes all new unknown students as a class of c+, the number of correct predictions in (2) will be equal to the N+, and the accuracy of this weak classifier A w will be equal to relative frequency p + :of dominant class c+:…”
Section: (1)mentioning
confidence: 99%
See 3 more Smart Citations